A FORM OF GASTROESOPHAGEAL EROSIVE REFLUX DISEASE: CLINICAL, ENDOSCOPIC, FUNCTIONAL AND IMMUNOMORPHOLOGICAL ASPECTS OF FORECASTING THE EMERGENCE AND COURSE OF ILLNESS - M. A. Osadchuk; S. N. Nikolenko (Сеченовский вестник, 2012)
The purpose of this research is the identification of new etiopathogenetic, diagnostic and prognostic data of erosive forms of gastroesophageal reflux disease. The total number of examined is 40 patients with erosive form of the illness and 60 with nonerosive, 30 patients with chronic gastritis and 20 are practically healthy. Erosive and nonerosive forms of the disease have similar pathogenetic variants, but having substantial quantitative differences in the parameters of diffuse neuroendocrine system and indicators of cellular renovation of epitheliocytes, top floor digestive tract indicators of proliferation causes the appearance and progression of erosive-ulcerous of defeats in the upper part of digestive tract.